2016
DOI: 10.48550/arxiv.1610.01257
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Deformation of matrix-valued orthogonal polynomials related to Gelfand pairs

Maarten van Pruijssen,
Pablo Román

Abstract: In this paper we present a method to obtain deformations of families of matrixvalued orthogonal polynomials that are associated to the representation theory of compact Gelfand pairs. These polynomials have the Sturm-Liouville property in the sense that they are simultaneous eigenfunctions of a symmetric second order differential operator and we deform this operator accordingly so that the deformed families also have the Sturm-Liouville property. Our strategy is to deform the system of spherical functions that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
(64 reference statements)
0
3
0
Order By: Relevance
“…The case of the matrix valued Hermite type polynomials of Section 3 does not fit into any of their examples. In [37] another approach of generalizing the results of [29], [30], is discussed. In particular, it is shown that the same polynomials of [31] are obtained in this way, and in [37] another decomposition of the weight is used.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The case of the matrix valued Hermite type polynomials of Section 3 does not fit into any of their examples. In [37] another approach of generalizing the results of [29], [30], is discussed. In particular, it is shown that the same polynomials of [31] are obtained in this way, and in [37] another decomposition of the weight is used.…”
Section: Introductionmentioning
confidence: 99%
“…In [37] another approach of generalizing the results of [29], [30], is discussed. In particular, it is shown that the same polynomials of [31] are obtained in this way, and in [37] another decomposition of the weight is used. However, shift operators and Rodrigues formulas are obtained.…”
Section: Introductionmentioning
confidence: 99%
“…In the rank one case, n = 1, one can show that the differential equation corresponding to the Casimir operator, see (2.8) below, is a so called matrix-valued hypergeometric differential operator, see e.g. [21,46] or [41,Rmk. 3.10].…”
Section: Matrix-valued Spherical Functionsmentioning
confidence: 99%